Nanoparticle-Based Rifampicin Delivery System Development - Motiei, Marjan; Pleno de Gouveia, Luis; Šopík, Tomáš; Vícha, Robert; Škoda, David; Císař, Jaroslav; Khalili, Reza; Domincová Bergerová, Eva; Münster, Lukáš; Fei, Haojie; Sedlařík, Vladimír; Sáha, Petr (Molecules (Basel, Switzerland), 2021)
The alkaline milieu of chronic wounds severely impairs the therapeutic effect of antibiotics, such as rifampicin; as such, the development of new drugs, or the smart delivery of existing drugs, is required. Herein, two innovative polyelectrolyte nanoparticles (PENs), composed of an amphiphilic chitosan core and a polycationic shell, were synthesized at alkaline pH, and in vitro performances were assessed by 1H NMR, elemental analysis, FT-IR, XRD, DSC, DLS, SEM, TEM, UV/Vis spectrophotometry, and HPLC. According to the results, the nanostructures exhibited different morphologies but similar physicochemical properties and release profiles. It was also hypothesized that the simultaneous use of the nanosystem and an antioxidant could be therapeutically beneficial. Therefore, the simultaneous effects of ascorbic acid and PENs were evaluated on the release profile and degradation of rifampicin, in which the results confirmed their synergistic protective effect at pH 8.5, as opposed to pH 7.4. Overall, this study highlighted the benefits of nanoparticulate development in the presence of antioxidants, at alkaline pH, as an efficient approach for decreasing rifampicin degradation.
Keywords: Rifampin; velikost částic; rifampicin; polyelectrolyte nanoparticles; polyelektrolyty; Calorimetry, Differential Scanning; Hydrogen-Ion Concentration; alkaline pH; Particle Size; statická elektřina; Proton Magnetic Resonance Spectroscopy; Nanoparticles; rifampin; vysokoúčinná kapalinová chromatografie; síran dextranu; Spectroscopy, Fourier Transform Infrared; spektrofotometrie ultrafialová; Dextran Sulfate; diferenciální skenovací kalorimetrie; Drug Liberation; nanočástice; Chromatography, High Pressure Liquid; spektroskopie infračervená s Fourierovou transformací; X-Ray Diffraction; difrakce rentgenového záření; Drug Delivery Systems; Spectrophotometry, Ultraviolet; Polyelectrolytes; lékové transportní systémy; uvolňování léčiv; ascorbic acid; koncentrace vodíkových iontů; Static Electricity; protonová magnetická rezonanční spektroskopie